Opening the Black Box: Task and Skill Mix and Productivity Dispersion - G. Jacob Blackwood; Cindy Cunningham; Matthew S. Dey; Lucia Foster; Cheryl Grim; John C. Haltiwanger; Rachel Nesbit; Sabrina Wulff Pabilonia; Jay Charles Stewart; Cody Tuttle; Zoltán Wolf (Institute of Labor Economics (IZA), 2022)
An important gap in most empirical studies of establishment-level productivity is the limited information about workers' characteristics and their tasks. Skill-adjusted labor input measures have been shown to be important for aggregate productivity measurement. Moreover, the theoretical literature on differences in production technologies across businesses increasingly emphasizes the task content of production. Our ultimate objective is to open this black box of tasks and skills at the establishment-level by combining establishment-level data on occupations from the Bureau of Labor Statistics (BLS) with a restricted-access establishment-level productivity dataset created by the BLS-Census Bureau Collaborative Micro-productivity Project. We take a first step toward this objective by exploring the conceptual, specification, and measurement issues to be confronted. We provide suggestive empirical analysis of the relationship between within-industry dispersion in productivity and tasks and skills. We find that within-industry productivity dispersion is strongly positively related to within-industry task/skill dispersion.
Keywords: D24; J24; J31; L60; 330; manufacturing; tasks; skills; productivity